(untitled) (Romano-arabica, 2025)
Teaching Arabic for academic purposes at the university level remains a largely neglected area and requires updated pedagogical approaches that address students’ academic needs in today’s world, especially amid the prevailing reliance on foreign languages in research. This study explores the key challenges students encounter when writing in Arabic, including limited access to specialized learning resources and insufficient language proficiency among advanced learners. Key reasons for this include the teaching methods through which they initially learned Arabic and the limited training in critical thinking skills, particularly critical reading and writing. Accordingly, the study advocates for the integration of critical reading as an effective means to enhance academic language proficiency. It will present the importance of critical reading in developing both analytical and linguistic skills, and propose an integrative approach built on three principles: critical language awareness, close reading, and functional grammar. This approach aims to refine learners’ understanding of how language functions in academic texts and support the production of high-quality writing that clearly articulates ideas. The study will also include an applied example for engaging with texts through critical reading.